Mechanical Performance Evaluation and Strengthening of Rectangular RC Columns with Deficient Lap Splices: Monotonic Loading Tests and Equivalent Plastic Hinge Modeling - Yuheng Zhao; Fangxin Jiang; Xue Zhang; Yufeng Guo (Buildings, 2025)
Reinforced concrete columns constructed prior to the 1970s often exhibit deficient lap splices at the base, characterized by insufficient splice lengths. In response to the urgent need for an efficient seismic assessment of these vulnerable structural elements, this study proposed a modelling method for lap-spliced columns. Typically, numerical simulations of columns with lap splices require the cross-sections of the lap-spliced and non-lap-spliced zones to be established, a process that is complex and time-consuming. This paper proposes an equivalent distribution of curvature along the height of the column to represent the effect of lap splice defects on the mechanical behavior of columns, thereby reducing the modelling complexity of such components. Four large-scale column specimens with varying lap splice lengths were subjected to monotonic pushover loading to investigate the effect of splice length on failure modes, strain distribution, and displacement ductility. An active strengthening method was employed to improve the performance of columns with deficient lap splices. Applying lateral prestress to the strengthening devices improves the mechanical behavior of columns. The experimental results revealed that insufficient splice lengths lead to reduced ductility and stress-transfer capacity. The strengthened specimen demonstrated significantly improved ductility and enhanced stress-transfer efficiency, indicating a marked improvement in mechanical performance. The proposed equivalent plastic hinge model was established in OpenSees. A database was created to verify the accuracy of the model. The results showed the modelling method to be accurate.